The Role of Personality in the Career Decision-Making Difficulties of Italian Young Adults. (May 2015) - Di Fabio, Annamaria; Palazzeschi, Letizia; Levin, Nimrod; Gati, Itamar
Both career-related developmental indecision and chronic indecisiveness are manifested in the difficulties individuals experience when choosing a career. Developmental career indecision is often regarded as a normal stage that many individuals undergo, regardless of individual differences in various personality factors. Testing this premise was the focus of this study. Specifically, the associations between career decision-making difficulties (Career Decision-Making Difficulties Questionnaire, a measure of developmental career indecision) and the Big Five personality factors were investigated among participants from three educational settings: 248 high school students, 167 on-the-job training (OJT) interns, and 186 university students. The results revealed that university students experience less developmental career indecision than high school students and OJT interns, suggesting that individuals' educational setting affects the prevalence of such difficulties. However, the personality factors of Extroversion and Neuroticism consistently explained a significantly larger percentage of variance in participants' developmental career indecision levels in all three samples than did educational setting or age. These results suggest that developmental career indecision may in fact be more personality related than previously thought.